2022
DOI: 10.3390/cells11244070
|View full text |Cite
|
Sign up to set email alerts
|

Histone Citrullination Mediates a Protective Role in Endothelium and Modulates Inflammation

Abstract: NETosis is a key host immune process against a pathogenic infection during innate immune activation, consisting of a neutrophil “explosion” and, consequently, NET formation, containing mainly DNA, histones, and other nuclear proteins. During sepsis, an exacerbated immune host response to an infection occurs, activating the innate immunity and NETosis events, which requires histone H3 citrullination. Our group compared the circulating histone levels with those citrullinated H3 levels in plasma samples of septic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…As described in the previous section, we selected genes showing differential methylation in between-group comparisons, appearing in enrichment analysis in the cnetplots maps and with relevant roles in immunosuppression. Genes selected from the previous section were investigated in terms of their biological relevance in sepsis, based on the different biological processes they were involved in, and the previous findings we and other authors have reported ( 3 5 ). This strategy allowed us to select the 10 most relevant candidates ( ILB1, IL10, IL17, IL18, IFNGR2, S100A8, S100A9, TNFAIP8, TREM1, IRAK3 ) for further validation through pyrosequencing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in the previous section, we selected genes showing differential methylation in between-group comparisons, appearing in enrichment analysis in the cnetplots maps and with relevant roles in immunosuppression. Genes selected from the previous section were investigated in terms of their biological relevance in sepsis, based on the different biological processes they were involved in, and the previous findings we and other authors have reported ( 3 5 ). This strategy allowed us to select the 10 most relevant candidates ( ILB1, IL10, IL17, IL18, IFNGR2, S100A8, S100A9, TNFAIP8, TREM1, IRAK3 ) for further validation through pyrosequencing.…”
Section: Resultsmentioning
confidence: 99%
“…The exacerbated hyper-inflammatory response can also damage non-infected tissues and lead to dysfunction of different organs and systems linked to hypotension, vasculature damage, and coagulation events, aggravating the disease status of septic patients, and producing early deaths at the initial stages of sepsis ( 2 ). The hyperinflammatory process is an acute event occurring usually at initial stages of sepsis just after infection ( 3 5 ). A compensatory anti-inflammatory response syndrome (CARS) can sometimes simultaneously occur, which can induce long-term immunosuppression, leading to secondary infections and most sepsis-associated late deaths ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…NETs contribute equally to thrombosis, immune response, and tissue damage, making them critical to the development of this disease. NETosis sets off platelets, leads to the release of toxic histones [ 101 , 171 , 172 , 173 ] and active enzymes, hence modifying thrombus stability [ 174 , 175 ]. The assembly of the inflammasome, along with heightened PAD4 activity, leads to the discharge of cytokines that are both pro-inflammatory and pro-thrombotic.…”
Section: Nex Stepsmentioning
confidence: 99%
“…NETosis sets off platelets, leads to the release of toxic histones (171)(172)(173) and active enzymes, hence modifying thrombus stability. (174,175) The assembly of the inflammasome, along with heightened PAD4 activity, leads to the discharge of cytokines that are both pro-inflammatory and pro-thrombotic. This also activates the endothelium, further increasing the recruitment of leukocytes as well as inflammasome assembly in adjacent cells.…”
Section: Conclusion and Next Stepsmentioning
confidence: 99%